Kola Sami language revitalisation - opportunities and challenges. - Scheller, Elisabeth (2013)
Today, all four Kola Sami languages are seriously endangered by a language shift from Sami to Russian. However, a language revitalisation process has started. Particularly the Kildin Sami language community in Lovozero seems to have the necessary political, financial and practical conditions for being able to carry out an effective language revitalisation, also in terms of a reintroduction of Kildin Sami as an everyday language of communication. But there are also challenges and barriers that have a braking effect on the revitalisation process. Historical events and political measures like collectivization, repressions, World War II, enforced resettlements and the boarding school system have still today a considerably destructive effect on the Kola Sami community and the language and cultural development. Other negative factors are purism, the lack of effective language teaching methods, unused resources and the promotion of the North Sami language among the Kola Sami. An important issue of the article is a critical discussion of the cooperation between Russian (Eastern) and Nordic (Western) Sápmi and what consequences non-transparent and irresponsibly implemented Western aid and development projects can have for the Kola Sami community and for the language and cultural revitalisation.